Withania somnifera (Ashwagandha) supplementation: a review of its mechanisms, health benefits, and role in sports performance - Mateusz Sprengel; Radosław Laskowski; Zbigniew Jost (Nutrition & Metabolism)
Abstract In recent years Withania somnifera (Ashwagandha) gained a lot of interest as an adaptogen, aiding sleep, stress management and presenting health and sports-related benefits. Although clinical effects have been previously reviewed, the specific mechanism of Ashwagandha’s action and its impact on different aspects of physical performance, body composition, as well as medical effects need more thorough analysis. Therefore, this narrative review delves into the available research examining the effects of Ashwagandha supplementation on such qualities as: strength, endurance, power, recovery, muscle mass, body fat, fertility, anxiety, metabolic health and aging, with additional focus on potential mechanisms underlying these effects. Moreover, we propose future perspectives based on the gaps observed in Ashwagandha research up to date.